SIKAP DAN PANDANGAN MASYARAKAT TERHADAP TERJEMAHAN AL-QUR’AN KEMENTERIAN AGAMA - Syatri, Jonni (Lajnah Pentashihan Mushaf Al-Qur'an, 2017)
This writing is a result of research on the attitude and society’s opinion on the translation of the Qur’an by the Ministry of Religious Affairs of the Republic of Indonesia. The focus of the research is to know and analyze the knowledge, understanding and attitude or society’s judgment on the translation of the Qur’an by the Ministry of Religious Affairs. Many of people are not aware that most of the Qur’anic translation being published by private publishers are the Qur’anic translation by the Ministry of Religious Affairs. To be seen from the aspect of translation, majority of people accept what has been done by the Ministry of Religious Affairs. However, among religious people and students, there many critical thinking and attitudes on the words of translation the Ministry of Religious Affairs. Therefore, the Ministry of Religious Affairs often get a critical and suggestive recommendations from many people for the betterment of the translation of the Qur’an of the Ministry of Religious Affairs. In addition to that, many of people hope that the Qur’anic translation can be equipped with some supplements such as Quranic sciences, footnotes, introduction of the surah, glossary, reference and guidance of using transliteration. Keywords: Qur’anic translation, Indonesian translation of the Qur’an, revision of translation